Curriculum: District stories of a path to improved achievement - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
A curriculum is not known to improve academic achievements. This book offers case studies of three Connecticut districts of high, medium and low socio-economic status, three districts from a national sample that won the prestigious Booker prize mainly representing low SES districts, and 10 districts that have implemented a Balanced Curriculum with a sample of various SES districts from high to low. All of them have used their curriculum as the vehicle toward improved achievements. The districts studied have four common themes, represented by the acronym "ASIA", for Alignment, Structure and Stability, Implementation and Infrastructure, and Assessment. All districts aligned their curriculum to state standards and assessments. They had a structure for the curriculum and had stability at the superintendent's position. The districts applied a lot of effort and attained results from implementing the curriculum and developing the infrastructure to support implementation, and they finally incorporated frequent district-wide assessments into their design. The book documents the subsets of these four areas that were present in most districts that might help other districts to replicate the findings. Research in the four areas is also documented. This book demonstrates through the case studies that it is possible to use curriculum as a framework for raising test scores. This is not normally thought of as a path to improved achievements. The fact that districts from a wide range of socio-economic statuses have used their curriculum to improve achievements demonstrates that a wider application of this direction could yield positive results for other districts. © 2014 by Nova Science Publishers, Inc. All rights reserved.
Keywords: dept.edl